Impact of Device Parameter Variation on the Electrical Characteristic of N-type Junctionless Nanowire Transistor with High-k Dielectrics - Sule, Mohammed Adamu; Ramakrishnan, Mathangi; Alias, Nurul Ezaila; Paraman, Norlina; Johari, Zaharah; Hamzah, Afiq; Tan, Michael Loong Peng; Sheikh, Usman Ulllah (IAES Indonesian Section, 2020)
Metallurgical junction and thermal budget are serious constraints in scaling and performance of conventional metal-oxide-semiconductor field-effect transistor (MOSFET). To overcome this problem, junctionless nanowire field-effect transistor (JLNWFET) was introduced. In this paper, we investigate the impact of device parameter variation on the performance of n-type JLNWFET with high-k dielectrics. The electrical characteristic of JLNWFET and the inversion-mode transistor of different gate length (LG) and nanowire diameter (dNW) was compared and analyzed. Different high-k dielectrics were used to get an optimum device structure of JLNWFET. The device was simulated using SDE Tool of Sentaurus TCAD and the I-V characteristics were simulated using Sdevice Tools. Lombardi mobility model and Philips unified mobility model were applied to define its electric field and doping dependent mobility degradation. A thin-film heavily doped silicon nanowire with a gate electrode that controls the flow of current between the source and drain was used. The proposed JLNWFET exhibits high ON-state current (ION) due to the high doping concentration (ND) of 1 x 1019 cm-3 which leads to the improved ON-state to OFF-state current ratio (ION/IOFF) of about 10% than the inversion-mode device for a LG of 7 nm and the silicon dNW of 6 nm. Electrical characteristics such are drain induced barrier lowering (DIBL) and subthreshold slope (SS) were extracted which leads to low leakage current as well as a high ION/IOFF ratio. The performance was improved by introducing silicon dioxide (SiO2) with high-k dielectric materials, hafnium oxide (HfO2) and silicon nitrate (Si3N4). It was found that JLNWFET with HfO2 exhibits better electrical characteristics and performance.